Rural electrification in protected areas: A spatial assessment of solar photovoltaic suitability using the fuzzy best worst method. (October 2021) - Minaei, Foad; Minaei, Masoud; Kougias, Ioannis; Shafizadeh-Moghadam, Hossein; Hosseini, Seyed Ali
Abstract: The need for energy in rural and remote areas is increasing, and it is exacerbated in developing countries. The wellbeing of communities and citizens depends on access to clean electricity to improve quality of life. An uninterrupted supply of electricity is one of the sustainable development goals (SDGs) that has highlighted the needs and challenges in remote areas. The complexity of designing strategies and solutions is further augmented for villages located in protected areas, national parks, and wildlife refuges, the conservation of which is fundamental to achieving climate, environmental, and ecologic objectives. Fossil fuel-based electricity generation and large-scale transmission networks pose a potential threat to the achievement of SDGs in such areas. This research investigated the use of solar photovoltaic (PV) technology as a renewable energy source (RES) that can cover energy needs of rural areas in a continuous, secure, and sustainable manner. In this study, the feasibility of using solar energy to electrify remote settlements located in protected areas of Iran (Khorasan-e-Razavi) was evaluated using a multi-criteria, GIS-based methodology. A set of criteria was selected to evaluate the suitability of solar PV, including solar irradiance and duration, aspect, temperature, precipitation, and humidity as well as proximity to faults, roads, and rivers. Using the best worth method (BWM), the relative weight of the selected criteria was calculated. The results showed that almost 2% of the region's area is very highly suitable and another 23.5% is highly suitable. This 25% represents an area of 1500 km 2 and includes 63 villages. Evaluation of census data showed that available building areas can cover the villages' residential demand using rooftop PV systems. Nonetheless, local and national government support is necessary to develop an effective strategy that results in successful implementation. Highlights: A fuzzy approach was used to evaluate influential factors of solar photovoltaic (PV) deployment. The Best-Worth Method (BWM) was employed to calculate the relative weights of selected factors. Build-up areas can cover villages' residential demand using rooftop PV systems. Integrating GIS and BWM proved to be an effective technique to create suitability maps.